The effect of outflows on CMB bounds from Primordial Black Hole accretion. Issue 12 (1st December 2022) - Piga, Lorenzo; Lucca, Matteo; Bellomo, Nicola; Bosch-Ramon, Valentí; Matarrese, Sabino; Raccanelli, Alvise; Verde, Licia
Abstract: Should Primordial Black Holes (PBHs) exist in nature, they would inevitably accrete baryonic matter in their vicinity. In turn, the consequent emission of high-energy radiation could affect the thermal history of the universe to an extent that can be probed with a number of cosmological observables such as the Cosmic Microwave Background (CMB) anisotropies. However, our understanding of the accretion and radiation emission processes in the context of PBHs is still in its infancy, and very large theoretical uncertainties affect the resulting constraints on the PBH abundance. Building on state-of-the-art literature, in this work we take a step towards the development of a more realistic picture of PBH accretion by accounting for the contribution of outflows. Specifically, we derive CMB-driven constraints on the PBH abundance for various accretion geometries, ionization models and mass distributions in absence and in presence of mechanical feedback and non-thermal emissions due to the outflows. As a result, we show that the presence of such outflows introduces an additional layer of uncertainty that needs to be taken into account when quoting cosmological constraints on the PBH abundance, with important consequences in particular in the LIGO-Virgo-KAGRA observational window.